Evolution of electrical conductivity in semi-interpenetrating polymer network of shape memory polyvinyl chloride and polyaniline - Wu, Xuelian (2023)
Electrically conductive semi-interpenetrating polymer network (IPN) from shape memory polyvinyl chloride (PVC) and polyaniline (PANI) is realized. The mechanical properties and shape memory performance of semi-IPN are slightly different from the original PVC. The distribution of PANI within PVC is found to be non-uniform in the thickness direction. The electrical conductivity of the as-fabricated sample at room temperature is around 4.5 × 10−2 S/cm. However, after heating, thermal strain results in significant drop in electrical conductivity. Programming remarkably reduces the electrical conductivity as well. A higher programming temperature and higher programming strain result in more reduction. Subsequent heating for shape recovery causes further reduction in electrical conductivity, despite nearly full shape recovery is achieved. Doping (dedoping and redoping) is confirmed not the major player, but microgaps/fracture in PANI chains during stretching in programming and heating for shape recovery.